2023
DOI: 10.3389/fcvm.2023.1208171
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear relationship between systemic inflammation response index and short-term mortality in patients with acute myocardial infarction: a retrospective study from MIMIC-IV

Abstract: BackgroundThis investigation aimed to evaluate the efficacy of the Systemic Inflammatory Response Index (SIRI) in prognosticating short-term all-cause mortality among patients diagnosed with acute myocardial infarction (AMI) in the intensive care unit (ICU).Methods and ResultsClinical data were obtained from the Medical Information Mart for Intensive Care-IV (MIMIC-IV) database. A total of 4,291 patients were included in the cohort. Results from multivariate regression analyses showed that the quartile of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…[ 127 ] Another recent study of 2023 investigating the performance of SIRI in patients with acute myocardial infarction with 4291 patients reported that SIRI was also an independent predictor of 30- and 90-day mortality with poor performance (AUC = 0.620, AUC = 0.624, respectively). [ 128 ] Another study examining the performance of SIRI in identifying acute coronary syndrome patients at high risk of a MACE also found that SIRI was an independent predictor of MACE with poor performance (AUC = 0.624). [ 129 ]…”
Section: Systemic Inflammation Response Indexmentioning
confidence: 99%
“…[ 127 ] Another recent study of 2023 investigating the performance of SIRI in patients with acute myocardial infarction with 4291 patients reported that SIRI was also an independent predictor of 30- and 90-day mortality with poor performance (AUC = 0.620, AUC = 0.624, respectively). [ 128 ] Another study examining the performance of SIRI in identifying acute coronary syndrome patients at high risk of a MACE also found that SIRI was an independent predictor of MACE with poor performance (AUC = 0.624). [ 129 ]…”
Section: Systemic Inflammation Response Indexmentioning
confidence: 99%
“…We then investigated the dose–response relationship using RCS analysis, and the result showed a positive non-linear relationship between SIRI and mortality. This non-linear relationship has also been noted in patients with myocardial infarction ( 24 ), asthma ( 27 ), and heart failure ( 38 ). Furthermore, the inflection points of ln (SIRI) among these studies were 2.9 (SIRI = 18.17) and 4.6 (SIRI = 99.48) for myocardial infarction ( 24 ), and 0.67 (SIRI = 1.95) for asthma ( 27 ).…”
Section: Discussionmentioning
confidence: 69%
“…Similar results in the full-adjustment models were found in older patients with heart failure for 90-day mortality (second tertile: HR = 1.31; third tertile: HR = 1.41), and 1-year mortality (second tertile: HR = 1.10; third tertile: HR = 1.19) ( 38 ). When patients were divided into four groups according to SIRI quartiles, the association in the second or third quartile lost the statistical significance in other studies ( 24 , 27 , 28 , 39 ). We then investigated the dose–response relationship using RCS analysis, and the result showed a positive non-linear relationship between SIRI and mortality.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In a similar population of ACS patients undergoing PCI, SIRI was confirmed as an independent determinant of MACE, which included all-cause mortality and re-hospitalization for severe heart failure, during the follow-up period (median follow-up duration was 1142 days) [ 2 ]. In AMI patients, multivariable Cox regression models evidenced the association between SIRI and short-term mortality (30 and 90 days) [ 9 ]. Both SII and SIRI were found to also be able to predict the risk of in-hospital death in elderly AMI patients [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%